Unmasking of oestrogen‐dependent changes in left ventricular structure and function in aged female rats: a potential model for pre‐heart failure with preserved ejection fraction. (12th February 2019) - Bustamante, Moises; Garate‐Carrillo, Alejandra; R. Ito, Bruce; Garcia, Ricardo; Carson, Nancy; Ceballos, Guillermo; Ramirez‐Sanchez, Israel; Omens, Jeffrey; Villarreal, Francisco
Abstract : Key points: Heart failure with preserved ejection fraction (HFpEF) is seen more frequently in older women; risk factors include age, hypertension and excess weight. No female animal models of early stage remodelling (pre‐HFpEF) have examined the effects that the convergence of such factors have on cardiac structure and function. In this study, we demonstrate that ageing can lead to the development of mild chamber remodelling, diffuse fibrosis and loss of diastolic function. The loss of oestrogens further aggravates such changes by leading to a notable drop in cardiac output (while preserving normal ejection fraction) in the presence of diffuse fibrosis that is more predominant in endocardium and is accompanied by papillary fibrosis. Excess weight did not markedly aggravate such findings. This animal model recapitulates many of the features recognized in older, female HFpEF patients and thus, may serve to examine the effects of candidate therapeutic agents. Abstract: Two‐thirds of patients with heart failure with preserved ejection fraction (HFpEF) are older women, and risk factors include hypertension and excess weight/obesity. Pathophysiological factors that drive early disease development (before heart failure ensues) remain obscure and female animal models are lacking. The study evaluated the intersecting roles of ageing, oestrogen depletion and excess weight on altering cardiac structure/function. Female, 18‐month‐old, Fischer F344 rats were divided into an aged group, aged + ovariectomy (OVX) and aged + ovariectomy + 10% fructose (OVF) in drinking water ( n = 8–16/group) to induce weight gain. Left ventricular (LV) structure/function was monitored by echocardiography. At 22 months of age, animals were anaesthetized and catheter‐based haemodynamics evaluated, followed by histological measures of chamber morphometry and collagen density. All aged animals developed hypertension. OVF animals increased body weight. Echocardiography only detected mild chamber remodelling with ageing while intraventricular pressure–volume loop analysis showed significant ( P < 0.05) decreases vs . ageing in stroke volume (13% OVX and 15% for OVF), stroke work (34% and 52%) and cardiac output (29% and 27%), and increases in relaxation time (10% OVX) with preserved ejection fraction. Histology indicated papillary and interstitial fibrosis with ageing, which was higher in the endocardium of OVX and OVF groups. With ageing, ovariectomy leads to the loss of diastolic and global LV function while preserving ejection fraction. This model recapitulates many cardiovascular features present in HFpEF patients and may help understand the roles that ageing and oestrogen depletion play in early (pre‐HFpEF) disease development. Key points: Heart failure with preserved ejection fraction (HFpEF) is seen more frequently in older women; risk factors include age, hypertension and excess weight. No female animal models of early stage remodelling (pre‐HFpEF) have examined the effects that the convergence of such factors have on cardiac structure and function. In this study, we demonstrate that ageing can lead to the development of mild chamber remodelling, diffuse fibrosis and loss of diastolic function. The loss of oestrogens further aggravates such changes by leading to a notable drop in cardiac output (while preserving normal ejection fraction) in the presence of diffuse fibrosis that is more predominant in endocardium and is accompanied by papillary fibrosis. Excess weight did not markedly aggravate such findings. This animal model recapitulates many of the features recognized in older, female HFpEF patients and thus, may serve to examine the effects of candidate therapeutic agents.